Importance of sampling frequency for the observed dynamics of SOC content in the Danish long-term monitoring network - Harbo, Laura Sofie; Lama, Rojina; Lemming, Camilla; Elsgaard, Lars (Geoderma Regional, 2025)
Monitoring soil organic carbon (SOC) content is crucial for understanding the role of agricultural soils in carbon sequestration and climate change mitigation. However, the influence of sampling frequency on the accuracy of SOC content trends remains an open question. This study investigates the effect of different sampling intervals using soils from the Danish long-term Soil Monitoring Network (SMN), which includes both decadal (every 10–12 years) and more frequent (7–11 times over 30 years) sampling since 1986, where the latter samples were originally collected (and archived) for analysis of soil mineral nitrogen. Our results show that decadal sampling effectively captures long-term SOC content trends, with no significant differences compared to more frequent sampling. Year-to-year variability in SOC content was high, suggesting that short-term fluctuations may mask long-term trends. This variability is reduced when SOC content trends are analysed over multi-year periods. To balance resource limitations with the need for temporal resolution, we suggest that a 3–5 year sampling scheme could be implemented, where a subset of SMN sites is sampled each year. This approach would provide finer temporal detail without the cost and effort of annual monitoring, while maintaining the ability to detect meaningful trends in SOC content dynamics. From an operational perspective, a rotational or rolling sampling strategy where only a fraction of sites (e.g., 20–30 %) are sampled each year such that all sites are eventually sampled in the monitoring period, would also help to maintain continuity of field expertise and laboratory capacity, ensuring consistent data quality over time. •No significant difference in long-term SOC trends between sampling frequencies.•Subsoil (25–50 cm) showed more consistent SOC trend increase than topsoil (0–25 cm).•SOC trends for data at one year apart showed high variability within each site.•The variability was reduced when SOC trends over multiple years were derived.